Real-World Next.js : build scalable, high-performance, and modern web applications using Next.js, the React framework for production - Riva, Michele (Packt Publishing, 2022)
Learn how to use Next.js for building web apps without compromising performance, user experience, and developer happiness Key Features Develop scalable web applications using Next.js Use Next.js as a frontend for existing backends and e-commerce websites and understand how to implement it with any headless CMS Deploy Next.js on different platforms, such as Vercel, DigitalOcean, and AWS, or on your own server Book Description Next.js is a scalable and high-performance React.js framework for modern web development and provides a large set of features, such as hybrid rendering, route prefetching, automatic image optimization, and internationalization, out of the box. If you are looking to create a blog, an e-commerce website, or a simple website, this book will show you how you can use the multipurpose Next.js framework to create an impressive user experience. Starting with the basics of Next.js, the book demonstrates how the framework can help you reach your development goals. You'll realize how versatile Next.js is as you build real-world applications with step-by-step explanations. This Next.js book will guide you in choosing the right rendering methodology for your website, securing it, and deploying it to different providers, all while focusing on performance and developer happiness. By the end of the book, you'll be able to design, build, and deploy modern architectures using Next.js with any headless CMS or data source. What you will learn Get up to speed with Next.js essentials and learn how to build apps quickly Understand how to create scalable Next.js architectures Choose between different rendering strategies, such as client-side rendering (CSR), static site generation (SSG), server-side rendering (SSR), and incremental static regeneration (ISR) Write unit tests and integration tests in your Next.js application Discover the powerful routing system and Next.js' built-in components Design and build modern architectures with Next.js using GraphCMS or any headless CMS Who this book is for This book is for web developers who want to improve their React skills by building scalable and maintainable full-stack applications using the modern Next.js web framework. Intermediate-level knowledge of ES6+, React, Node.js, and REST is assumed.